2013
DOI: 10.1021/ol401779h
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Regioselective C–H Alkenylation Directed by a Free Amino Group

Abstract: The ruthenium-catalyzed alkenylation reactions of 2-aminobiphenyls and cumylamine proceed smoothly to produce the corresponding regioselectively alkenylated products. These reactions involve a C-H bond cleavage directed by their free amino groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…[1] An amino group itself or an itrogen functionality derived thereof can coordinate to am etal, thus acting as the directing group,a sac omplexinduced proximity effect [2] arises between the metal and aspecific CÀHb ond of the amine.Inf act, specific C(sp 2 )ÀH bonds of primary [3] and secondary [4] amines are amenable to transition metal catalyzed functionalization. [1] An amino group itself or an itrogen functionality derived thereof can coordinate to am etal, thus acting as the directing group,a sac omplexinduced proximity effect [2] arises between the metal and aspecific CÀHb ond of the amine.Inf act, specific C(sp 2 )ÀH bonds of primary [3] and secondary [4] amines are amenable to transition metal catalyzed functionalization.…”
mentioning
confidence: 99%
“…[1] An amino group itself or an itrogen functionality derived thereof can coordinate to am etal, thus acting as the directing group,a sac omplexinduced proximity effect [2] arises between the metal and aspecific CÀHb ond of the amine.Inf act, specific C(sp 2 )ÀH bonds of primary [3] and secondary [4] amines are amenable to transition metal catalyzed functionalization. [1] An amino group itself or an itrogen functionality derived thereof can coordinate to am etal, thus acting as the directing group,a sac omplexinduced proximity effect [2] arises between the metal and aspecific CÀHb ond of the amine.Inf act, specific C(sp 2 )ÀH bonds of primary [3] and secondary [4] amines are amenable to transition metal catalyzed functionalization.…”
mentioning
confidence: 99%
“…In our experiments, we did not observe Miura's alkenylation product IX due to absence of a proton source. 28 Luan's dibenzo [b,d]azepines X, which are formed through reductive elimination from III, were also not formed under our conditions. Why the reaction proceeded along a different pathway under our conditions remains unclear, but it is likely that under our conditions performed in dichloromethane (b.p.…”
mentioning
confidence: 66%
“…[27] In this context, Miura reported the Ru-catalyzed amine-directed alkenylation of o-arylanilines with internal alkynes (Scheme 1a). [28] Subsequently , Luan demonstrated the palla-1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 dium-catalyzed [5 + 2] oxidative annulation of oarylanilines with alkynes to obtain dibenzo[b,d]azepines (Scheme 1b). [29] We developed an efficient palladium-catalyzed [2 + 2 + 2] cycloaddition of Nsubstituted o-arylanilines with diarylacetylenes to obtain multisubstituted naphthalenes.…”
mentioning
confidence: 99%
“…Therefore, the transitionmetal-catalyzed chelation-assisted aromatic CÀH functionalization through a cyclometalation should be an ideal strategy to meet these substantial challenges. [4,5] In addition, the N,N-dimethylaminomethyl group has been disclosed as a directing group for both oxidative Heck and arylation reactions. [3] Very recently, Miura et al and Jiao et al have reported that primary anilines can serve as a directing group for ortho CÀH olefination and azidation, respectively.…”
mentioning
confidence: 99%
“…[3] Very recently, Miura et al and Jiao et al have reported that primary anilines can serve as a directing group for ortho CÀH olefination and azidation, respectively. [4,5] In addition, the N,N-dimethylaminomethyl group has been disclosed as a directing group for both oxidative Heck and arylation reactions. [6] However, the transition-metal-catalyzed C À H activation of tertiary anilines remains less developed except for few examples on para-selective transformations [7] and the recently reported oxidative ortho CÀH alkenylation/N-dealkylative carbonylation of tertiary anilines (tertiary amines probably act as a directing group).…”
mentioning
confidence: 99%